ANALISIS PERCOBAAN TINDAK PIDANA PEMBUNUHAN (PUTUSAN NO. 3250/Pid.B/2021/PN Mdn): Analysis of Attempted Criminal Acts of Murder (Decision No.3250/Pid.B/2021/PN Mdn) - Muhammad Firza; Maria Silvya E. Wangga (Faculty of Law, Universitas Trisakti, 2025)
An attempted crime refers to an effort to realize a criminal objective that ultimately fails. In Decision No. 3250/Pid.B/2021/PN Mdn, the perpetrator attempted murder by attacking the victim with blows and a knife aimed at the neck, causing life-threatening injuries. The act was halted when Sinuraya intervened, prompting the perpetrator to flee. The panel of judges imposed a five-year prison sentence; however, this study considers the punishment inappropriate, as sentencing must reflect the gravity of the offender’s actions. This research employs a normative juridical method with a descriptive-analytical approach. The findings indicate that the elements of attempted murder were fulfilled, including intent, commencement of execution, and interruption of the act due to external intervention. Thus, the perpetrator’s conduct constitutes a stopped attempt. Nonetheless, the five-year sentence is inconsistent with Article 338 in conjunction with Article 53(2) of the Indonesian Criminal Code. The proper sentencing calculation is two-thirds of the principal penalty for murder, amounting to ten years’ imprisonment. Therefore, the judicial decision should have more accurately reflected proportionality based on the form of attempted crime involved.